1995
DOI: 10.1002/j.2048-7940.1995.tb01627.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Characteristics of Patients with Completed Stroke: Those Who Achieve Continence and Those Who Do Not

Abstract: The purpose of this retrospective study was to compare the demographic, neurologic, and cognitive characteristics of patients with completed stroke who participated in a behavioral management program for urinary incontinence. The study sought to determine the differences between those patients who achieved continence by the time of discharge from the program and those who did not. A retrospective chart review that used the Functional Independence Measure (FIM) scores identified 75 subjects with urinary inconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
4
1
2
Order By: Relevance
“…The patients in this study reflected an association between UI and poorer poststroke outcomes identified in previous research (Gelberet al, 1993; Jongbloed, 1986; Owen et al, 1995). The subjects for whom UI persisted throughout their rehabilitation program exhibited lower functional status scores at discharge and made less improvement during rehabilitation.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The patients in this study reflected an association between UI and poorer poststroke outcomes identified in previous research (Gelberet al, 1993; Jongbloed, 1986; Owen et al, 1995). The subjects for whom UI persisted throughout their rehabilitation program exhibited lower functional status scores at discharge and made less improvement during rehabilitation.…”
Section: Discussionsupporting
confidence: 60%
“…This study extends the work of Owen et al (1995) by comparing outcomes measured at set intervals from the time of stroke onset. In addition, this study describes and compares patients’ progress in rehabilitation based on their continence status at discharge.…”
Section: Literature Reviewmentioning
confidence: 76%
See 2 more Smart Citations
“…Much has been written about functional outcomes in rehabilitation (Chae, Zorowitz, & Johnston, 1996; Cook, Smith, & Truman, 1994; Frost & Barone, 1996; Goldstein, Strasser, Woodard, & Roberts, 1997; Hanks & Lichtenberg, 1996; Hinkle & Forbes, 1996; Owen, Getz, & Bulla, 1995; Stineman, Maislin, Fiedler, & Granger, 1997; Ween, Alexander, D'Esposito, & Roberts, 1996). Jaworski, Kult, and Boynton (1994) report that “a functional assessment tool is commonly used to establish a patient's baseline functional level and to evaluate whether rehabilitation outcomes have been attained during rehabilitation” (p. 141).…”
Section: Review Of the Literaturementioning
confidence: 99%